Pengaruh Kualitas Sumber Daya Manusia Dan Efektivitas Penggunaan Instagram Terhadap Pengembangan Umkm Kuliner Di Kota Palu - Albar. S, Nadira; Mahardiana, Lina; Ibrahim, Andi Indriani; Islianty, Nur Risky (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of human resource quality and the effectiveness of Instagram usage on the development of culinary MSMEs in Palu City. Using a quantitative associative approach, data were collected from 71 culinary MSME owners selected through purposive sampling and analyzed using multiple linear regression. The findings reveal that human resource quality and Instagram usage effectiveness positively and significantly affect culinary MSME development, both partially and simultaneously. Human resource quality shows a more dominant influence. These results imply that strengthening entrepreneurial competencies and optimizing Instagram-based digital marketing can support sustainable MSME growth and enhance business competitiveness in the digital era. Keywords: Human Resource Quality; Instagram Effectiveness; Social Media Marketing; Digital Marketing; Culinary MSMEs; MSME Development; Entrepreneurial Competence; Palu City